1988
DOI: 10.1111/j.1365-2621.1988.tb07813.x
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as Proteinase Carriers for the Accelerated Ripening of Saint‐Paulin Type Cheese

Abstract: The possibility of accelerated cheese ripening through addition of liposome entrapped proteinase to milk was investigated. Both enzyme encapsulation rate in liposomes and their retention in cheese were evaluated with multilamellar vesicles (MLV) and reverse-phase evaporation vesicles (REV). Using REV in Saint-Paulin type curd, no nitrogen loss was observed to the whey due to the added enzymes in liposomes. In cheese, REV produced a more progressive proteolysis during ripening than MLV did. REV addition did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
11
0
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 18 publications
5
11
0
2
Order By: Relevance
“…The retention rates of the two gums are comparable to that of dehydrated-rehydrated (DRV) liposomes (90%), the highest reported for liposomes (Kirby et al, 1987). The retention rates for both gums and milk fat in this study were higher than those observed by Alkhalaf et al(1988) for free Neutrase in cheeses (20%).…”
Section: Retention Of Capsules In Cheese Curdsupporting
confidence: 83%
“…The retention rates of the two gums are comparable to that of dehydrated-rehydrated (DRV) liposomes (90%), the highest reported for liposomes (Kirby et al, 1987). The retention rates for both gums and milk fat in this study were higher than those observed by Alkhalaf et al(1988) for free Neutrase in cheeses (20%).…”
Section: Retention Of Capsules In Cheese Curdsupporting
confidence: 83%
“…Even though this difference was not found to be significant, table 1 shows the same trend, which suggests a slight, early proteolysis, inducing a decrease in protein retention in the curd. This observation is consistent with the lower dry matter content (P < 0.05) in cheeses containing liposomes (table 1). An increase in moisture in liposome-treated chee ses has been reported [18,28].…”
Section: Efficiency Of Enzyme Immobilizationsupporting
confidence: 79%
“…The technique is not food grade and the organic solvent can denature the enzyme (Szoka & Papahadjopoulous, 1978). Enzyme encapsulation efficiencies of $30% have been achieved as well as curd entrapment levels of 42% (Alkhalaf et al, 1988(Alkhalaf et al, , 1989.…”
Section: Enzyme Encapsulationmentioning
confidence: 97%